Study of Elemental Depth Distribution in the Multilayer Material \(\text{TiO}_2\)/\(\text{SiO}_2\)/Si by Rutherford Backscattering Spectrometry (RBS) - Phuc, T. V.; Kulik, M.; Kobzev, A. P.; Khiem, L. H. (Communications in Physics, 2019)
In this study we investigated depth distributions of elements in the multilayer structures of TiO\(_2\)/SiO\(_2\)/Si before and after ion irradiation. The samples were implanted with Ne\(^+\), Ar\(^+\), Kr\(^+\) and Xe\(^+\) ions. For each implantation the multilayer structures were irradiated by the ions with the energy 100, 150, 200 and 250 keV. The elemental concentrations in the samples were analyzed by the Rutherford Backscattering Spectrometry (RBS) method. It was found that the transition layers existed between the TiO\(_2\) and SiO\(_2\) layers. Formation of these layers derived from the ion beam mixing that was occurred at TiO\(_2\)/SiO\(_2\) interface after irradiation process. The depth profiles show that thickness of the transition layers increased with the growing energy and atomic mass of the implanted ions.